# What is the answer for question 7) ? http://postimg.org/image/xusvq33e3/

### 1 Answer | Add Yours

To do this we need to know the following rules.

`log_a(b) = 1/(log_b(a))` ---(1)

`log_a(b^n) = nlog_a(b)` ----(2)

Now moving to our question we can say;

`3/(log_2(a)) = 3log_a2`

`2/(log_4(a)) = 2log_a4= 2log_a(2^2) = 4log_a(2)`

`3/(log_2(a))-2/(log_4(a))`

`= 3log_a2-4log_a(2)`

`= -log_a(2)`

`= log_a(2^(-1))` from (2)

`= log_a(1/2)`

`= 1/(log_(1/2)(a))` from (1)

*So the statement is true.*

`3/(log_2(a))-2/(log_4(a)) = 1/(log_(1/2)(a))`

**Sources:**